2021
DOI: 10.1016/j.jpsychires.2021.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to address mental health issues in healthcare workers during infectious disease outbreaks: A systematic review

Abstract: Considering the importance of evidence on interventions to tackle mental health problems in healthcare workers (HCWs) during pandemics, we conducted a systematic review, aiming to identify and summarize the implemented interventions to deal with mental health issues of HCWs during infectious disease outbreaks and report their effectiveness. Web of Science, PubMed, Cochrane, Scopus, CINAHL and PsycInfo electronic databases were searched until October 2 nd , 2020. Primary-data articles, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
81
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 53 publications
5
81
0
3
Order By: Relevance
“…Many studies have reported that positive coping or other practices could relieve the psychological impact (Zaçe et al, 2021). The same finding was noticed in this study, improving active coping skills and other planful problem-solving coping support measures and decreasing the self-blame influence of distress symptoms on HPDE will be useful; however, HPDE nurses need more support to manage these confrontive coping influences.…”
Section: Discussionsupporting
confidence: 81%
“…Many studies have reported that positive coping or other practices could relieve the psychological impact (Zaçe et al, 2021). The same finding was noticed in this study, improving active coping skills and other planful problem-solving coping support measures and decreasing the self-blame influence of distress symptoms on HPDE will be useful; however, HPDE nurses need more support to manage these confrontive coping influences.…”
Section: Discussionsupporting
confidence: 81%
“…We suggest some implications for practice that may help organisations to better support their professionals. However, future research is needed to assess the effectivity of specific interventions to support frontline workers [ 41 , 42 ]. Participants’ narratives illustrate that working in the frontline was emotionally demanding, but sharing experiences and close connections with colleagues seemed to mitigate psychological distress among frontline workers.…”
Section: Discussionmentioning
confidence: 99%
“…Intervention strategies for burnout should focus on modifications in the organizational structure at professional environment and on the promotion of healthy attitudes [ 17 , 20 ]. A recent systematic review by Zaçe et al [35] aimed to identify and outline the implemented interventions addressing psychiatric disorders among healthcare workers during different epidemics and pandemics, including the actual COVID-19. The authors identified four main categories of intervention, which are informational support, instrumental support, organizational support, and emotional and psychological interventions.…”
Section: Discussionmentioning
confidence: 99%